Molecular contribution to cleft palate production in cleft lip mice. (May 2014) - Sasaki, Yasunori; Taya, Yuji; Saito, Kan; Fujita, Kazuya; Aoba, Takaaki; Fujiwara, Taku
Abstract Cleft palate following cleft lip may include a developmental disorder during palatogenesis. CL/Fr mice fetuses, which develop cleft lip and palate spontaneously, have less capability for in vivo cell proliferation in palatal mesenchyme compared with CL/Fr normal fetuses. In order to know the changes of signaling molecules contributing to cleft palate morphogenesis following cleft lip, the mRNA expression profiles were compared in palatal shelves oriented vertically (before elevation) in CL/Fr fetuses with or without cleft lip. The changes in mRNA profile of cleft palate morphogenesis were presented in a microarray analysis, and genes were restricted to lists contributing to cleft palate development in CL/Fr fetuses with cleft lip. Four candidate genes (Ywhab, Nek2, Tacc1 and Frk) were linked in a gene network that associates with cell proliferation (cell cycle, MAPK, Wnt and Tgf beta pathways). Quantitative real‐time RT‐PCR highlighted the candidate genes that significantly changed in CL/Fr fetuses with cleft lip (Ywhab, Nek2 and Tacc1). The results of these molecular contributions will provide useful information for a better understanding of palatogenesis in cleft palate following cleft lip. Our data indicated the genetic contribution to cleft palate morphogenesis following cleft lip.